ANALYSIS OF LANDSLIDE POTENTIAL IN GUNUNG OMEH SUB-DISTRICK LIMA PULUH KOTA REGENCY USING HVSR METHOD - Nabilla, Agma; Syafriani, Syafriani (Al-Fiziya: Journal of Materials Science, Geophysics, Instrumentation and Theoretical Physics, 2023)
On BPBD Lima Puluh Kota designated Gunung Omeh Sub-district as a disaster-prone area due to the detected potential of moving soil. This mobile soil causes gaps in the soil with the potential to continue to move at any time and is exacerbated by unstable soil conditions that cause the risk of landslides. Therefore, there is a need for research in Gunung Omeh sub-district on landslide potential. This research aims to analyse the landslide potential in Gunung Omeh sub-district. Data collection is limited to 9 measurement points using a set of Sysmatrack MAE seismograph sensor type S3S. The data generated is in the form of seismic wave signals which are then processed with the HVSR method using Geopsy software to produce H/V curves with parameters A0 and f0. From these two parameters, the values of soil susceptibility index (Kg) and ground shear strain (γg) are obtained. The results showed that the susceptibility index ranged from 0.26 x 10-6 s2/cm to 16.34 x 10-6 s2/cm and ground shear strain ranged from 1.32 x 10-4 to 2.15 x 10-6. Thus, the highest landslide potential is found at point 6 with the highest susceptibility index of 16.34994479 and ground shear strain of 1.32x10¬4.